Lung perfusion characteristics in pulmonary arterial hypertension (PAH) and peripheral forms of chronic thromboembolic pulmonary hypertension (pCTEPH): Dual-energy CT experience in 31 patients. - Giordano, Jessica; Khung, Suonita; Duhamel, Alain; Hossein-Foucher, Claude; Bellèvre, Dimitri; Lamblin, Nicolas; Remy, Jacques; Remy-Jardin, Martine (European Radiology, 2017)
Purpose: To compare lung perfusion in PAH and pCTEPH on dual-energy CT (DECT) examinations.Materials and Methods: Thirty-one patients with PAH (group 1; n = 19) and pCTEPH (group 2; n = 12) underwent a dual-energy chest CTA with reconstruction of diagnostic and perfusion images. Perfusion alterations were analysed at a segmental level. V/Q scintigraphy was available in 22 patients (group 1: 13/19; group 2: 9/12).Results: CT perfusion was abnormal in 52.6 % of group 1 patients and in 100 % of group 2 patients (p = 0.0051). The patterns of perfusion alteration significantly differed between the two groups (p < 0.0001): (1) in group 1, 96.6 % of segments with abnormal perfusion showed patchy defects; (2) in group 2, the most frequent abnormalities consisted of patchy (58.5 %) and PE-type (37.5 %) defects. Paired comparison of CT perfusion and scintigraphy showed concordant findings in 76.9 % of group 1 (10/13) and 100 % of group 2 (9/9) patients, with a predominant or an exclusive patchy pattern in group 1 and a mixed pattern of abnormalities in group 2.Conclusion: Lung perfusion alterations at DECT are less frequent and more homogeneous in PAH than in pCTEPH, with a high level of concordant findings with V/Q scintigraphy.Key Points: • Depiction of chronic pulmonary embolism exclusively located on peripheral arteries is difficult. • The main differential diagnosis of pCTEPH is PAH. • The pattern of DECT perfusion changes can help differentiate PAH and pCETPH. • In PAH, almost all segments with abnormal perfusion showed patchy defects. • In pCTEPH, patchy and PE-type defects were the most frequent abnormalities.